A Review: Laser-Processed Polymers for Biomedical Applications - Maysam Abbood Salman Al-Abassli; Rafi Abdul- Majeed Al -Razzuqi (American Journal of Botany and Bioengineering, 2026)
In addition to their usage in the creation of medical devices, polymer materials hold great promise for advancing a number of critical biomedical applications, most notably tissue engineering. This paper comprises of a general review on laser applications for biomedical using biopolymers, which are natural or synthetic polymers derived from biological sources. They are safe, less toxic and comparatively simple. In this paper, laser processes of polymer biomaterials for hard and soft tissue applications are discussed based on a set of criteria, with biocompatibility being the most important aspect. The paper concludes case studies of laser operations involving different types of medical polymers, as well as the challenges and future directions facing biomedical applications.